Cytotoxic lesion of the corpus callosum in a patient with aphasic status epilepticus: Lesión citotóxica del cuerpo calloso en un paciente con estado epiléptico afásico - Castiglione, Juan-Ignacio; Ricciardi, Mario-Emiliano; Bensi, Catalina (Journal of Applied Cognitive Neuroscience, 2020)
A 47-year-old man with a history of aphasic seizures presented to the emergency room with a 12-hour global aphasia. Upon admission, brain MRI did not reveal acute lesions, and EEG showed sharp waves in the left frontal-temporal region. An Aphasic Status Epilepticus was diagnosed and antiepileptic treatment was initiated with adequate response. A week after the episode, a new brain MRI showed a high-signal ovoid lesion on T2-weighted and FLAIR sequences in the central part of the splenium of the corpus callosum. On diffusion-weighted images (DWI) the lesion was hyperintense with decreased apparent diffusion coefficient (ADC) values, indicating restricted diffusion consistent with a cytotoxic lesion of the corpus callosum (CLOCC). Follow-up MRI one month later showed complete image resolution. CLOCCs are secondary lesions associated with various entities in which high levels of cytokines and extracellular glutamate cause intracellular edema and reduced diffusion, a condition called cytotoxic edema, which affects vulnerable brain regions such as the splenium of the corpus callosum. In epileptic patients, CLOCCs may be due to the effect of seizures, especially prolonged ones, as well as antiepileptic treatment itself. CLOCCs are rare radiological findings and must be recognized to avoid misdiagnosis.